Spectroscopic studies of the vibrational and electronic properties of solid hydrogen to 285 GPa - Goncharov, Alexander F. (The National Academy of Sciences, 2001)
We report Raman scattering and visible to near-infrared absorption spectra of solid hydrogen under static pressure up to 285 GPa between 20 and 140 K. We obtain pressure dependences of vibron and phonon modes consistent with results previously determined to lower pressures. The results indicate the stability of the ordered molecular phase III to the highest pressure reached and provide constraints on the insulator-to-metal transition pressure.